Self-Reported Hearing Loss and Pure Tone Audiometry for Screening in Primary Health Care Clinics - Christine Louw; De Wet Swanepoel; Robert H Eikelboom (SAGE Publishing, 2018)
Objective: To evaluate the performance of self-reported hearing loss alone and in combination with pure tone audiometry screening in primary health care clinics in South Africa. Design: Nonprobability purposive sampling was used at 2 primary health care clinics. A total of 1084 participants (mean age 41.2 years; SD 15.5 years; range 16-97 years, 74.0% female) were screened using self-report and audiometry screening. Those failing audiometric screening and a sample of those who passed audiometric screening were also assessed by diagnostic pure time audiometry, to confirm or negate the finding of a hearing loss. Results: Four hundred and thirty-six participants (40.2%) self-reported a hearing loss with no significant association with gender or race. One hundred and thirty-six participant (12.5%) self-reported hearing loss and failed audiometry screening (35 dB HL at 1, 2, and 4 kHz). Combining self-report with a second stage audiometry screening revealed a high test accuracy (81.0%) for hearing loss, being most accurate (86.1%) to identify high-frequency hearing loss. Conclusion: While self-report of hearing loss is an easy and time-efficient screening method to use at primary health care clinics, its accuracy may be limited when used in isolation and it may not be sufficiently sensitive to detect hearing loss. Combining a simple audiometry screening as a second-stage screen can significantly improve overall performance and efficiency of the screening protocol.